Transcriptomic insights into the effects of tyrosine on sub-Columbian plumage in H line chickens - Wang, Xinlei; Zhang, Liheng; Yang, Liyu; Yang, Pengkun; Qiao, Yingying; Han, Zhanbing; Fan, Jiaying; Li, Qiang; Zhang, Dingding; Li, Zhuanjian; Kang, Xiangtao; Du, Juan; et al. (Frontiers in Veterinary Science, 2025)
Tyrosine is known to influence melanin generation; however, its involvement in melanin production in chicken feathers is unknown. We evaluated the feather color of H-line chickens fed diets containing different concentrations of tyrosine (0, 0.4, 0.6, 0.8, and 1.0%). The results indicated that a diet containing 1.0% tyrosine fed for 40 days significantly increased melanin deposition in the feathers (p < 0.05). Following this observation, we collected feather follicle tissue from chickens fed either 0% or 1.0% tyrosine at the 40-day time point for transcriptome sequencing. RNA-seq analysis identified a total of 314 DEGs, comprising 116 upregulated and 198 downregulated genes. KEGG analysis of feather follicle tissue revealed that 7 DEGs (EDNRB2, WNT3, POMC, INS, FLT3, CACNA2D3, and CACNA1I) mapped to melanin-related pathways, including the melanogenesis, MAPK signaling and Wnt signaling pathways. We also identified specific protein interactions within the melanin pathway, including EDNRB2–MLPH and WNT3–FGF16 interactions. Notably, the expression level of the EDNRB2 gene reached its peak at 10 weeks within the 0–12 week growth period in H-line chickens. In primary chicken melanocytes, EDNRB2 expression was quantified following tyrosine supplementation and was found to be markedly elevated at a concentration of 10−6 mol/L, significantly higher than the control and other treatment groups (p < 0.05). Overall, our findings suggest the significant involvement of the tyrosine-induced EDNRB2 regulatory network in melanin levels in sub-Columbian plumage. Taken together, these findings increase our understanding of the molecular mechanisms that regulate tyrosine-mediated melanin deposition in chicken plumage.